Clinical characteristics and outcomes of left ventricular pseudoaneurysm: A retrospective study in a single-center of China. Issue 18 (May 2017) - Meng, Xu; Yang, Yan-Kun; Yang, Kun-Qi; Zhang, Ying; Lu, Pei-Pei; Fan, Peng; Ma, Li-Hong; Zhou, Xian-Liang
Abstract : Abstract: Left ventricular (LV) pseudoaneurysm is a fatal and rare condition with a high risk of rupture. The symptoms are nonspecific and diagnosis is often delayed. The purpose of this study is to analysis a series of cases in our institution. Between March 2009 and April 2016, 10 patients (5 males and 5 females) with LV pseudoaneurysm were retrospectively enrolled. Clinical information, diagnostic imaging modalities, treatment, and outcomes were evaluated. The mean age was 58.2 ± 11.0 years (28–71 years). The common symptoms were chest pain (3 cases), dyspnea (3 cases), and syncope (2 cases). All patients had nonspecific abnormalities on the electrocardiogram, and 7 patients had chest X-ray abnormalities. Three etiologies including myocardial infarction (6 cases), mitral valve replacement (3 cases), and suspected endocarditis (1 case) were identified. LV pseudoanerysm was diagnosed in 8 patients by transthoracic echocardiography, and the other 2 patients were diagnosed by computed tomography angiogram. Posterior (4 cases) and lateral (4 cases) of the left ventricle were the most common positions of the rupture orifice. Eight patients accepted surgery repair and 2 patients were treated conservatively. In 2 patients, residual apical aneurysm was found, 1 patient was detected with a residual LV pseudoaneurysm, and 1 patient had myocardial infarction at 61 months' follow-up. Myocardial infarction was the most common etiology of patients with LV pseudoaneurysm. The most frequently ruptured orifices were lateral and posterior walls of the left ventricle. Surgery is recommended as the first option, and conservative therapy can be considered for appropriate patients.